Nghiên cứu lí thuyết cơ chế phản ứng giữa gốc propargyl với gốc hydroxyl bằng phương pháp phiếm hàm mật độ - Tiến, Phạm Văn; Long, Lê Kim; Minh Huệ, Nguyễn Thị (Vietnam Journal of Chemistry, 2014)
The reaction mechanism of the Propargyl radical and Hydroxyl radical has been studied by the Density Functional Theory (DFT) using the B3LYP functional in conjunction with the 6-311++G(d,p) and 6-311++G(3df,2p) basis sets. The potential energy surface (PES) for the C3H3 and OH system was also established. Calculated results indicate that products of this reaction can be (H2CCC+H2O), (HCCCH+H2O), (CH4+C2O), (HCCCHO+H2), (C2H2 + HCHO), (H2CCCO+H2) and (C2H4+CO). However, the formation of (C2H4+CO) is the most favorable. Keywords: Reaction mechanism, propargyl radical, hydroxyl radical, density functional theory.